2022
DOI: 10.2147/prbm.s346470
|View full text |Cite
|
Sign up to set email alerts
|

Negative Influences of Differentiated Empowering Leadership on Team Members’ Helping Behaviors: The Mediating Effects of Envy and Contempt

Abstract: Purpose: Given the popularity of empowerment practices among scholars and practitioners, this research examines whether a manager's differentiated empowering leadership negatively affects team members' helping behaviors and, if so, how. Methods: The authors conducted one multi-source and time-lagged survey (with 44 managers and 212 team members) and two scenario-based experiments (with 120 participants in Study 2 and 121 participants in Study 3) to test the research model. Results: Team managers' differentiate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…While previous research has predominantly focused on the positive effects of empowering leadership on team outcomes (e.g., Amoroso et al, 2021; Hsu et al, 2023; Tang et al, 2020), there is a growing recognition of the need to include both the potential benefits and costs associated with this leadership approach into consideration (e.g., Cheong et al, 2019). As emerging research sheds light on the potential negative effects of empowering leadership on team-level helping behavior (Sun et al, 2022), scholars have gradually recognized that empowerment can be dysfunctional for optimal team functioning. Although prior studies have demonstrated inconsistent findings of empowering leadership at the team level (i.e., team performance), our understanding of how empowerment manifests these paradoxical effects was limited.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While previous research has predominantly focused on the positive effects of empowering leadership on team outcomes (e.g., Amoroso et al, 2021; Hsu et al, 2023; Tang et al, 2020), there is a growing recognition of the need to include both the potential benefits and costs associated with this leadership approach into consideration (e.g., Cheong et al, 2019). As emerging research sheds light on the potential negative effects of empowering leadership on team-level helping behavior (Sun et al, 2022), scholars have gradually recognized that empowerment can be dysfunctional for optimal team functioning. Although prior studies have demonstrated inconsistent findings of empowering leadership at the team level (i.e., team performance), our understanding of how empowerment manifests these paradoxical effects was limited.…”
Section: Discussionmentioning
confidence: 99%
“…M. Lin et al, 2022; Tang et al, 2020). However, emerging research revealed the potential negative impact of empowering leadership on team consequences (e.g., team performance, Han et al, 2022; helping behavior, Sun et al, 2022), suggesting that empowerment may not always be beneficial in optimizing team functioning. Given this conflicting pattern of findings, scholars called for greater attention to the effectiveness of empowering leadership at the team level (e.g., Cheong et al, 2019) to consider how (via what mediators or intervening variables) and when (in the presence of what moderators) empowering leadership might lead to higher or lower team consequences, especially team performance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In study 1, a situational experiment has been designed to examine the causal relationship between FWC and SAW, which is a method with high internal validity and can be used to test causal conclusions. 39 After that, in order to ensure the external validity of the research results, in study 2, a two-wave and time-lagged field study has been designed, this study examined the full conceptual model, 40 including the mediating role of OFTP and the mediating role of FWAP. The research results of different methods are combined to ensure the validity and generalization of the research results.…”
Section: Hypothesismentioning
confidence: 99%
“…The individual level focused on the employee behavior and found the personal characteristics as key factor to explain the effect of leadership empowerment. While some scholars argue that empowering leadership behaviors may have negative consequences, such as employee misconduct [4] , Sun suggests that disparities in empowering leadership can lead to an unequal distribution of power, damaging employee relationships, triggering negative emotions such as, jealousy and contempt, and reducing employees' inclination to assist others [5] . Chen et al contend that employee conflicts can diminish the positive effects of empowering leadership on innovative behavior and may even negatively impact empowering leadership when conflicts escalate to a certain degree [6] .…”
Section: Individual-levelmentioning
confidence: 99%